Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/mnfr.201900927
|View full text |Cite
|
Sign up to set email alerts
|

Mastiha (Pistacia lentiscus) Improves Gut Microbiota Diversity, Hepatic Steatosis, and Disease Activity in a Biopsy‐Confirmed Mouse Model of Advanced Non‐Alcoholic Steatohepatitis and Fibrosis

Abstract: ScopeAs a result of the obesity epidemic, the prevalence of non‐alcoholic steatohepatitis (NASH) is increasing. No drug is approved for the treatment of NASH. In this study, the effect of a nutritional supplement, Mastiha or Chios mastic gum, on metabolic and histological parameters and on the gut microbiome in mice with NASH and fibrosis was investigated.Methods and resultsAdvanced NASH was induced by feeding C57BL/6J mice a diet rich in fat, sucrose, and cholesterol for 41 weeks. After randomization, animals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Mastiha or Chios mastic gum, a kind of natural food obtained from Pistacia lentiscus, was found to be beneficial in the treatment of advanced NASH in mice by decreasing alanine transaminase (ALT) level and NAS score. [100] It is noteworthy that Mastiha treated mice exhibit a recovery of microbiome diversity and a slight change in gut microbiota composition. [100] In a rat model of NAFLD, the Chinese medicine Qushi Huayu decoction and its key bioactive compounds (geniposide and chlorogenic acid) significantly improved the gut barrier and decreased liver lipid synthesis by enhancing the enrichment of Treg-inducing bacteria and beneficial intestinal bacteria, suggesting a gut microbiota-modulated mechanism of herbal medicines in the treatment of NAFLD.…”
Section: Herbal Medicinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mastiha or Chios mastic gum, a kind of natural food obtained from Pistacia lentiscus, was found to be beneficial in the treatment of advanced NASH in mice by decreasing alanine transaminase (ALT) level and NAS score. [100] It is noteworthy that Mastiha treated mice exhibit a recovery of microbiome diversity and a slight change in gut microbiota composition. [100] In a rat model of NAFLD, the Chinese medicine Qushi Huayu decoction and its key bioactive compounds (geniposide and chlorogenic acid) significantly improved the gut barrier and decreased liver lipid synthesis by enhancing the enrichment of Treg-inducing bacteria and beneficial intestinal bacteria, suggesting a gut microbiota-modulated mechanism of herbal medicines in the treatment of NAFLD.…”
Section: Herbal Medicinesmentioning
confidence: 99%
“…[100] It is noteworthy that Mastiha treated mice exhibit a recovery of microbiome diversity and a slight change in gut microbiota composition. [100] In a rat model of NAFLD, the Chinese medicine Qushi Huayu decoction and its key bioactive compounds (geniposide and chlorogenic acid) significantly improved the gut barrier and decreased liver lipid synthesis by enhancing the enrichment of Treg-inducing bacteria and beneficial intestinal bacteria, suggesting a gut microbiota-modulated mechanism of herbal medicines in the treatment of NAFLD. [101] Yang et al demonstrated that the major ingredients of the Dachaihu decoction, including Chinese thorowax, scutellaria, and white peony roots, reduce pro-inflammatory cytokine expression in the liver and maintain the intestinal barrier to protect against liver injury in www.advancedsciencenews.com www.mnf-journal.com Table 2.…”
Section: Herbal Medicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our structural studies of GN probe binding to ASGPR and HSA provide a basis for probe optimization not only for imaging studies but also potentially for liver-specific drug delivery via ASGPR. [46][47][48] Overall, we describe a complete toolkit including "first-inclass" chemical imaging probes to launch new lines of preclinical investigation into the molecular pathways of NASH onset and progression as well as to more effectively explore and understand the impact of treatment intervention in a more relevant in vivo model which will significantly aid the translation of preclinical research into the clinical setting.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of P. lentiscus was investigated in mice with obesity, nonalcoholic steatohepatitis (NASH), and liver fibrosis induced by HFD. Treatment with P. lentiscus promoted a partial but significant recovery of microbiota diversity associated with a decrease in Bacteroidia and an increase in Proteobacteria relative abundance [154].…”
Section: Microbiota-modulating Plantsmentioning
confidence: 96%